Dynamics and Structure of Halogen-Bonded Cocrystals: Synthesis, Solid-State NMR, and X-ray Diffraction - Gunaga, Shubha (Université d'Ottawa | University of Ottawa, 2024)
Supramolecular chemistry explores the use of intermolecular noncovalent bonds, focusing on entities formed by associating multiple chemical species to construct supramolecular assemblies. Among these bonds, the halogen bond (XB) has attracted significant interest for its role in shaping these assemblies. The presence of the σ-hole positioned opposite to a C-X covalent bond (X most commonly being I, Br, or Cl) endows the halogen bond with exceptional directional and tunable properties. This feature appeals to crystal engineers aiming for precise control in molecular assemblies. Advances in the areas of crystal engineering and crystal structure prediction have paved the pathway for innovative applications harnessing halogen bonding. These applications span diverse fields such as catalysis, liquid crystals, drug delivery, protein-ligand complexes, pharmaceutical science, functional materials, molecular gyroscopes, and dynamics involved in these different systems, showcasing the vast potential of exploiting the halogen bonding. Dynamics, with its ubiquitous presence in nature has long captivated researchers driving their pursuit to understand and decipher the intricate rate of reactions unravelling the complexities of chemical kinetics and gain insights into how reactions occur at the molecular level. Dynamic processes play a crucial role in dictating the functionality of various materials. This thesis examines the halogen bond, its nature, its role in supramolecular assembly, and impact on molecular dynamics. We also explore synthetic methods for materials dependent on this interaction, and investigate the modulation of methyl rotational dynamics, shedding light on the influence of noncovalent halogen bonds in these dynamics. Our exploration commences with the design and synthesis of a novel series of cocrystalline architectures incorporating halogen bonds to deuterated tetramethylpyrazine (TMP) utilizing gas phase, solution, and solid state mechanochemical methods. Powder X-ray diffraction methods are used to confirm the phase purity of these samples. We have successfully solved the single crystal X-ray structures of this novel series featuring a cocrystal involving molecular bromine as well as weak chloro halogen bond (XB) donors, which serve as strong directional structural directing elements. We have made use of static deuterium solid-state NMR experiments over a wide range of temperatures to measure T₁ time constants and then calculated the rotational barrier of methyl groups located near the halogen bond. The experimentally determined methyl rotational activation energy (Eₐ) for the range of halogen bonded cocrystals, when compared to the halogen bond acceptor reference molecule, reveals a significant reduction in the energy barrier upon the introduction of the halogen bond. Computational studies employing linear transit calculations have shown that electronic factors significantly influence the Eₐ calculated for the XB systems examined here. Furthermore, careful consideration of satellite atoms positioned around the methyl groups also impacts Eₐ, by acting as a steric factor. Our meticulous examination of the average number of carbon-carbon close contacts to the methyl group, a pivotal steric factor, has rationalized the observed trends in the chloro-, bromo- and iodo- XB series. This finding offers an excellent approach to potentially understanding and controlling the dynamics in molecular machines, supramolecular catalysts, and biochemical systems. By modulating the number of carbon-carbon close contacts by altering the stoichiometry of designed cocrystal synthons while maintaining the core chemical features, new opportunities to design complex geared or cascade dynamics involving larger functional groups found in e.g., metal-organic frameworks, engineered rotors, protein and enzymes are created. The role of the halogen bond in crystal engineering was then further explored. We report another novel cocrystal of 2,3,5,6-tetramethylpyrazine and 1,3,4,5-tetrabromo-2,6-difluorobenzene showcasing type II halogen bonding. We have studied the structural features of this system using single crystal X-ray diffraction and computations. Infinite chains of approximately coplanar donor and acceptor molecules are held by Br···N halogen bonds and bromine in positions 3 and 5 of the halogen bond donor molecule acts simultaneously as a halogen bond donor and acceptor. This results in a herringbone arrangement of the infinite chains influenced by crystal packing; halogen bond strength and pedal motion ability suggests potential for greater thermal expansion. The findings underscore the significance of developing novel aromatic-based solids specifically crafted for electronic applications.
Keywords: SSNMR; deuterium SSNMR; methyl dynamics; X-ray diffraction; halogen bond; cocrystals